Homiletic and Exegetical Approach of St Pionius in His Martyr's Act - Петков, Ангел (Forum Theologicum Sardicense, 2025)
Angel Petkov, Homiletic and Exegetic Approach of St. Pionius (in His Martyr’s Atc). Christian martyr Pionius is a prominent figure in the Early Church. His homily, recorded in his Martyrium, is noted for its rational approach, and his exegesis of the Old Testament is grounded in historical analysis.